Phenylbutazone blood and urine concentrations, pharmacokinetics, and effects on biomarkers of inflammation in horses following intravenous and oral administration of clinical doses. Issue 6 (27th December 2018) - Knych, Heather K.; Arthur, Rick M.; McKemie, Dan S.; Seminoff, Kelsey; Hamamoto‐Hardman, Briana; Kass, Philip H.
Abstract: Phenylbutazone (PBZ) is a potent mon‐steroidal anti‐inflammatory drug used commonly in performance horses. The objectives of the current study were to describe blood and urine concentrations and the pharmacokinetics of PBZ and its metabolites following intravenous (IV) and oral administration and to describe the duration of pharmacodynamic effect. To that end, 17 horses received an IV administration and 18 horses an oral administration of 2 g of PBZ. Blood and urine samples were collected prior to and for up to 96 hours post drug administration. Whole blood samples were collected at various time points and challenged with lipopolysaccharide or calcium ionophore to induce ex vivo synthesis of eicosanoids. Concentrations of PBZ and eicosanoids were measured using liquid chromatography–tandem mass spectrometry (LC–MS/MS) and non‐compartmental pharmacokinetic analysis performed on concentration data from IV and oral administration. Serum concentrations of PBZ and its metabolites were below the limit of quantitation at 96 hours post administration. The volume of distribution at steady state, systemic clearance, and terminal half‐life was 0.194 ± 0.019 L/kg, 23.9 ± 4.48 mL/h/kg, and 10.9 ± 5.32 hours, respectively. The terminal half‐life following oral administration was 13.4 ± 3.01 (paste) and 15.1 ± 3.96 hours (tablets). Stimulation of PBZ treated whole blood with lipopolysaccharide and calcium ionophore resulted in an inhibition of TXB2, PGE2, LTB4 and 15‐HETE production for a prolonged period of time post drug administration. The results of this study suggest that PBZ has a prolonged anti‐inflammatory following IV or oral administration of 2 g to horses. Abstract : Following intravenous and oral administration of 2 g of phenylbutazone to horses, serum concentrations were below the LOQ by 96 hours. Prolonged inhibition of a number of eicosanoids, including TXB2, PGE2, LTB4, and 15(S)‐HETE was observed in serum collected from horses treated with phenylbutazone following ex vivo stimulation with LPS and calcium ionophore.